Analysis of Patient Follow-Up at a Level I Trauma Center in Ohio. Issue 6 (November 2017) - Fletcher, Brian; Meyers, Tami; Guilliams, Michelle; Poliseno, Teresa; Burton, Josh; Lieber, Michael; Buggie, Ed; O'Mara, M. Shay
Abstract : Trauma patients report being unprepared for hospital discharge. The purpose of this study was to identify follow-up compliance rates at our trauma clinic and identify factors associated with trauma patients' adherence to follow-up appointment. We recruited patients 15 years and older who were discharged from the trauma service between December 2014 and August 2015. Demographic information and injury-related variables were obtained from the trauma registry for patients who attended their follow-up and those who did not attend. Follow-up appointment weather data were collected. All patients were surveyed regarding barriers to compliance. There was no difference in demographics, number of intensive care unit days, length of stay, or distance to the clinic. On days with rain or snow, patients were less likely to follow-up. Patients were more likely to follow-up on warmer days, and maximum daily air temperature was an independent predictor of follow-up compliance. Mechanism of injury and trauma activations were associated with higher follow-up compliance. Trauma patients are overall compliant with postdischarge follow-up appointments. There are no consistent factors related to trauma follow-up when compared with similar follow-up studies.